Key Binding Interactions for Memantine in the NMDA Receptor - Limapichat, Walrati (American Chemical Society, 2012)
[Image: see text] Memantine (Namenda) is prescribed as a treatment for moderate to severe Alzheimer’s Disease. Memantine functions by blocking the NMDA receptor, but the key binding interactions between drug and receptor are not fully elucidated. To determine key binding interactions of memantine, we made side-by-side comparisons of IC(50) for memantine and amantadine, a structurally related drug, in the GluN1/GluN2B NMDA receptor. We identified hydrophobic binding pockets for the two methyl groups on memantine formed by the residues A645 and A644 on the third transmembrane helices of GluN1 and GluN2B, respectively. Moreover, we found that while adding two methyl groups to amantadine to produce memantine greatly improves affinity, adding a third methyl group to produce the symmetrical trimethylamantadine diminished affinity. Our results provide a better understanding of chemical-scale interactions between memantine and the NMDA channel, which will potentially benefit the development of new drugs for neurodegenerative diseases involving NMDA receptors.